Genes related to high temperature tolerance during maize seed germination - Dutra, S. M. F. [UNESP]; Von Pinho, E. V. R.; Santos, H. O.; Lima, A. C.; Von Pinho, R. G.; Carvalho, M. L. M. (Funpec-editora, 2015)
The identification of genes related to heat tolerance is fundamental for the development of high-quality seeds that are tolerant to heat stress condition. The objective of this study was to evaluate maize lineages and the gene expression involved in high temperature tolerance during germination using physiological tests, proteomics, and transcriptome analysis. Seeds from six maize lineages (30, 44, 54, 63, 64, and 91) with different levels of tolerance to high temperatures were used. Lineages 54 and 91 were observed to be more tolerant to high temperature conditions. The highest expression of alpha-amylase was observed in maize seeds from lineages 30 and 91 that were subjected to controlled deterioration. The highest expression of a-amylase was observed in maize seeds from lineages 30 and 91 that were subjected to controlled deterioration; with the controlled deterioration, the highest level of gene expression did not occur in the most tolerant materials; the association of lower expression of genes involved in heat-resistant protein systems was observed in seeds from lineage 44, which were more susceptible to high temperatures, and the highest gene expression of LEA D-34, ZmAN13, and AOX-1 was observed in seeds from lineage 64 when submitted to controlled deterioration.
Keywords: RT-qPCR; Proteomics; Abiotic stress